2021
DOI: 10.21203/rs.3.rs-690372/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of anti-SARS-CoV-2 antibodies among blood donors in South Africa during the period January-May 2021

Abstract: Background: Population-level estimates of the prevalence of anti-SARS-CoV-2 antibody positivity (seroprevalence) are crucial epidemiological indicators for tracking the Covid-19 epidemic. Such data are in short supply, both internationally and in South Africa. The South African blood services (the South African National Blood Service, SANBS and the Western Cape Blood Service, WCBS) are coordinating nationwide surveillance of blood donors. Methods: Leveraging existing arrangements, SANBS human research ethics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The primary limitation of this study is that changes in testing practices, health-seeking behavior, or access to care have not been accounted for in these analyses. Estimates based on serological data from blood donors suggest substantial geographic variability in detection rates ( 19 ), which may contribute to the observed differences in reinfection patterns by province (Supplementary Figure S1). Detection rates likely also vary through time and by other factors affecting access to testing, which may include occupation, age, and socioeconomic status.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…The primary limitation of this study is that changes in testing practices, health-seeking behavior, or access to care have not been accounted for in these analyses. Estimates based on serological data from blood donors suggest substantial geographic variability in detection rates ( 19 ), which may contribute to the observed differences in reinfection patterns by province (Supplementary Figure S1). Detection rates likely also vary through time and by other factors affecting access to testing, which may include occupation, age, and socioeconomic status.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Anticipating that a fourth wave late in 2021 was inevitable (though there was no knowledge of the omicron variant at the time of planning), 3395 specimens were randomly collected from consenting donors from all provinces except the Western Cape (which has its own separate blood service) presenting to donate blood to the South African National Blood Service (SANBS) from 8 to 12 November 2021. This was carried out in accordance with previous arrangements and practices underlying our previous rounds of sampling [1,2], as approved by the SANBS Human Research Ethics Committee (HREC).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously published estimates of the prevalence of anti-SARS-CoV-2 antibodies among blood donors in South Africa, based on specimens collected from January to May 2021 [1,2], as well as estimates of fatality rates, based on these prevalence estimates and publicly available excess deaths estimates [3].…”
Section: Introductionmentioning
confidence: 99%
“…Early estimates suggested that the Beta variant had a transmission rate of 23-50% compared to ancestral lineages [159]. Seroprevalence estimates from blood donor surveys ranged from 32% to 62% across South Africa's nine provinces, with a weighted national estimate of 47% following the second wave peak in January 2021 [160]. A report on SARS-CoV-2 variant transmission in Switzerland estimated a 50% increase in transmissibility [103].…”
Section: Transmissibilitymentioning
confidence: 99%
“…When compared to White people in the COVID-19 study, those of the Black race and those who live in impoverished neighborhoods were identified as population categories that may be more vulnerable to the unfavorable influence of PM 2.5 on hospitalization risk [368]. In a study conducted in South Africa by Vermeulen et al (2021) (data from 16,762 test blood donations received between January and May 2021 for anti-SARS-CoV-2 antibodies) seroprevalence in Black donors was consistently several times higher than in White donors, with the other major population groups (Colored and Asian) not well represented in any regions [160].…”
Section: Population Density Race and Life Conditionmentioning
confidence: 99%